2015
DOI: 10.1159/000381472
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Longevity and in Responses to Anti-Aging Interventions: A Mini-Review

Abstract: A robust, often underappreciated, feature of human biology is that women live longer than men not just in technologically advanced, low-mortality countries such as those in Europe or North America, but across low- and high-mortality countries of the modern world as well as through history. Women's survival advantage is not due to protection from one or a few diseases. Women die at lower rates than men from virtually all the top causes of death with the notable exception of Alzheimer's disease, to which women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 48 publications
4
107
0
3
Order By: Relevance
“…This feminization of old age occurred always in history and in various parts of the world. (15) The mean age of the sample involved in this study was 68 ± 7 years, with a prevalence of 60 to 69 years (51.9%), as also observed in other studies. (16)(17)(18) Most of the subjects in our research reported only up to three years of school education (86.5%), which sets the difficulty of school access, historically presented by Brazilian low-income population, especially regarding the women.…”
Section: Discussionsupporting
confidence: 83%
“…This feminization of old age occurred always in history and in various parts of the world. (15) The mean age of the sample involved in this study was 68 ± 7 years, with a prevalence of 60 to 69 years (51.9%), as also observed in other studies. (16)(17)(18) Most of the subjects in our research reported only up to three years of school education (86.5%), which sets the difficulty of school access, historically presented by Brazilian low-income population, especially regarding the women.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding lifestyle habits, few elderly people reported smoking and alcohol consumption, which may be explained by the predominance of females in the sample, considering that women devote more attention to health and self-care [20, 21]. According to the IPAQ, most of participants were considered active, diverging from other studies in which the level of physical activity is presented inversely proportional to income and education [33, 34].…”
Section: Discussionmentioning
confidence: 87%
“…The great number of females in old age is associated with several aspects, such as less exposure to occupational risk factors, lower prevalence of smoking and alcoholism, greater attention to health and self-care, and greater frequency of using the health services [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Data going back centuries in several European countries show that a substantial difference in life expectancy between men and women has been consistently present. 21,22 Women live longer and this has been shown to be true for 176 countries and geopolitical units out of 178 in Unstats.un.org. 23 Starting with this observation, those within the sociologist camp have explored the disparity in male/ female longevity in terms of social cause.…”
Section: A Classic Case As Seen From the Sociological Versus The Biolmentioning
confidence: 99%